Effect of traditional and resisted sprint training in highly trained female team handball players - Luteberget, L. S.; Raastad, T.; Seynnes, O.; Spencer, M. (International Journal of Sports Physiology and Performance, 2015)
Fast acceleration is an important performance factor in handball. In addition to traditional sprint training (TST), resisted-sprint training (RST) is a method often used to improve acceleration. However, studies on RST show conflicting results, and underlying mechanisms have not been studied. Purpose: To compare the effects of RST, by sled towing, against TST on sprint performance and muscle architecture. Methods: Participants (n = 18) were assigned to either RST or TST and completed 2 training sessions of RST or TST per week (10 wk), in addition to their normal team training. Sprint tests (10 and 30 m) and measurements of muscle architecture were performed pre- and posttraining. Results: Beneficial effects were found in the 30-m-sprint test for both groups (mean; ±90% CL: TST = -0.31; ±0.19 s, RST = -0.16; ±0.13 s), with unclear differences between the groups. Only TST had a beneficial effect on 10-m time (-0.04; ±0.04 s), with a likely difference between the 2 groups (85%, ES = 0.60). Both groups had a decrease in pennation angle (-6.0; ±3.3% for TST and -2.8; ±2.0% for RST), which had a nearly perfect correlation with percentage change in 10-m-sprint performance (r = .92). A small increase in fascicle length (5.3; ±3.9% and 4.0; ±2.1% for TST and RST, respectively) was found, with unclear differences between groups. Discussion: TST appears to be more effective than RST in enhancing 10-m-sprint time. Both groups showed similar effects in 30-m-sprint time. A similar, yet small, effect of sprint training on muscle architecture was observed in both groups.